Future Well-Being Among U.S. Youth Who Attempted Suicide and Survived. Issue 3 (May 2022) - Tong, Bingjie; Devendorf, Andrew; Panaite, Vanessa; Miller, Rose; Kashdan, Todd B.; Joiner, Thomas; Twenge, Jean; Karver, Marc; Janakiraman, Roshni; Rottenberg, Jonathan
Highlights: Little is known about healthy functioning after nonfatal suicide attempts. Suicide attempts reduced but did not preclude high levels of future well-being. Baseline well-being, not depression, predicted future well-being among survivors. We recommend incorporating well-being into suicide assessment and intervention. Abstract: To what extent does a suicide attempt impair a person's future well-being? We estimated the prevalence of future well-being (FWB) among suicide attempt survivors using a nationally representative sample of 15, 170 youths. Suicide attempt survivors were classified as having high FWB if they reported (a) a suicide attempt at Wave I, (b) no suicidal ideation or attempts over the past year at Wave III (7 years after), and (c) a well-being profile at or above the top quartile of nonsuicidal peers. Seventy-five of 574 suicide attempt survivors (∼13%) met criteria for FWB at Wave III, compared to 26% of nonsuicidal peers. Wave I well-being levels, not depressive symptoms, predicted the likelihood of FWB at Wave III ( OR  = 1.23, 95% CI [1.05, 1.44], p  < .05). In conclusion, a nonfatal suicide attempt reduced but did not preclude FWB in a large national sample. The observation that a segment of the population of suicide attempt survivors achieves FWB carries implications for the prognosis of suicidal behavior and the value of incorporating well-being into investigations of suicide-related phenomena.